(untitled) (Journal of the College of Basic Education, 2023)
The researchers focused on studying the political, economic and social history of the Arab world.As well as studying the political figures who played positive or negative roles.Political history, I meant their studies with political fluctuations, wars and foreign relations for thiscountry or that country, but it neglected the study of democratic experiences, and since the democratic experienceIn the Arab world, it has not yet matured as a result of subjective and objective factors.This type of research is important in that it sheds light on the development of the councils’ experience.local affairs in Yemen and the conditions and circumstances that Yemen went through in its contemporary history.What encouraged me to write was my presence in brotherly Yemen in the years 2003-2004 and my closeness toSources and references related to the subject.